Intrauterine balloon tamponade in the management of atonic postpartum haemorrhage: case study from a tertiary care hospital - Rupali A Gaikwad; Shrinivas N Gadappa (Barpeta Obstetrics and Gynaecological Society, 2021)
Objective: Objective of the study was to study the efficacy of condom tamponade to arrest bleeding in cases of atonic postpartum haemorrhage (PPH) unresponsive to uterotonics. Methods: We conducted prospective observational study, in the Department of Obstetrics and Gynecology of Govt. Medical college & hospital, Aurangabad for 2 yrs. UBT (uterine balloon tamponade) was applied to women who developed atonic PPH following childbirth unresponsive to uterotonics. UBT was inflated with normal saline. Clinical success was defined as control of bleeding following balloon insertion without further intervention. Results: Out of the 385 women who had atonic PPH, 63 were managed with insertion of condom balloon catheter after failed medical management. Success rate was 61 out of 63 cases (96.8%). In 3 cases bleeding persisted even after 30 minutes and surgical intervention done for 2 of the 3 cases; in the third patient bleeding was arrested 30 minutes after tamponade application (1.63%). In 9 (14.2%) patients UBT was expelled spontaneously within 6 hours, out of it 2 required further surgical intervention due to uncontrolled PPH. In 93.6% cases bleeding got controlled within 15 -30 mins of condom tamponade insertion, the balloon was inflated for an average of 18 hours before removal. Conclusions: Condom catheter is a noninvasive, effective, conservative method of PPH management. In cases of failure it provides a temporary tamponade effect and time to prepare for other interventions.